Response of anaerobic granular sludge to single-wall carbon nanotube exposure - Li, Ling-Li; Tong, Zhong-Hua; Fang, Cai-Yun; Chu, Jian; Yu, Han-Qing (Water research (Oxford), 2015)
Rapid development and application of nanotechnology have introduced various nanopaticles, such as single-walled carbon nanotubes (SWCNTs), whose negative effects on aquatic organisms and cultured cells have been reported, into anaerobic wastewater treatment systems. In this study, the response of methanogenic sludge exposed to SWCNTs in anaerobic digestion process was investigated. Results show that SWCNTs, at a concentration up to 1000 mg/L, had no significant impact on the maximum methane yield. In contrast, they induced much faster substrate utilization and methane production rates. Scanning electron microscopy examination shows that more extracellular polymeric substances (EPS) were excreted from the anaerobic sludge and closely interacted with SWCNTs. Such an interaction prevented nanoparticles from piercing into cells, and thus reduced their cytotoxicity. In the compact anaerobic granule structure, SWCNTs exposure enhanced the electrical conductance of the sludge, which might promote direct interspecies electron transfer among anaerobic fermentative bacteria and methanogens in the anaerobic digestion process. Our results provide useful information to understand the response of anaerobic microorganisms to CNTs in complex environmental matrix. [Display omitted] •SWCNTs had no impact on the maximum methane yield of anaerobic sludge.•Much faster substrate utilization and methane production rates with SWCNT dosing.•SWCNTs enhanced the electrical conductance of the sludge.•SWCNTs might promote direct interspecies electron transfer among the anaerobes.